Effectiveness and Safety of Dupilumab and Tralokinumab for Treating Atopic Dermatitis and Pruritic Skin Disorders in Oncological Patients: A Narrative Review - Lauletta G; Potestio L; Patruno C; De Lucia M; Napolitano M (Clinical, Cosmetic and Investigational Dermatology)
Giuseppe Lauletta,1 Luca Potestio,1 Cataldo Patruno,2 Mario De Lucia,1 Maddalena Napolitano1 1Section of Dermatology - Department of Clinical Medicine and Surgery, University of Naples Federico II, Naples, Italy; 2Department of Medicine and Health Sciences “Vincenzo Tiberio”, University of Molise, Campobasso, ItalyCorrespondence: Luca Potestio, Section of Dermatology - Department of Clinical Medicine and Surgery, University of Naples Federico II, Via Pansini 5, Napoli, 80131, Italy, Tel +39 - 081 – 7462457, Fax +39 - 081 – 7462442, Email potestioluca@gmail.comIntroduction: Atopic dermatitis (AD) and pruritic skin disorders are increasingly recognized in cancer patients. The management of these conditions in patients with a history or with concomitant cancer presents unique challenges, as traditional systemic therapies may pose risks due to their immunosuppressive effects. In recent years, biologic agents such as dupilumab and tralokinumab have emerged as promising treatments for AD, offering targeted modulation of the immune response with potentially fewer systemic side effects. This article aims to review the current evidence on the safety and efficacy of dupilumab and tralokinumab in treating AD and pruritus among cancer survivors, addressing the potential benefits and considerations for this unique patient population.Methods: A comprehensive analysis of the current medical literature was performed on the PubMed, Ovid, Scopus, Embase, and Cochrane Library databases until December 15, 2024. In conducting this narrative review, Medical Subject Headings (MeSH) terms and medical terminology related to clinical trials and real-life studies were employed, focusing on the pharmacological agents dupilumab, and tralokinumab.Discussion: Patients with active or past cancer are typically excluded from clinical trials of new medications, complicating the evaluation of cancer progression or recurrence risks in these patients setting. The potential use of biologic drugs like dupilumab and tralokinumab in oncological patients marks a significant breakthrough for treating conditions such as eczema and pruritus, which are common in this patient group. Although there are no explicit contraindications for using dupilumab and tralokinumab in patients with active cancer or a history of malignancy, there is no definitive guidance on their use in such cases. Real-world data is emerging, facilitated by collaboration between dermatologists and oncologists, supporting the effectiveness and safety of dupilumab and tralokinumab for managing AD in cancer patients. Nonetheless, larger studies with longer follow-up periods and dedicated pharmacovigilance programs are needed to substantiate these findings.Keywords: atopic dermatitis, dupilumab, tralokinumab, oncological patients